THE PROBLEM OF LEGAL REGULATION OF THE INSTITUTION OF THE FIRST LADY IN THE USA, FRANCE AND UKRAINE - Hapak, Nataliia; Tkach , Tetiana (Collection of scientific papers «ΛΌГOΣ», 2023)
One of the main problems in establishing the institution of the First Lady is the legal framework for this issue.